Dynamics of Non-Litigation Law Resolution in the Juvenile Criminal Justice System - Kimico Margaretha Tjhia; Suparno Suparno (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Handling children in conflict with the law in the juvenile criminal justice system requires a more humane and restorative approach. The purpose of this study is to analyze the application of diversion in the juvenile criminal justice system and identify the challenges faced. This research uses normative legal research method with statutory approach and case analysis. The results show that although diversion has been regulated in the law, its implementation still faces various obstacles, such as lack of understanding among law enforcers, community stigma towards children, and resistance from the justice system itself. Efforts to overcome these obstacles include education and socialization to the community as well as training for law enforcers. This research underscores the importance of support from all relevant parties, including law enforcement, the community, and the child family, to ensure the success of the diversion process. Better knowledge of the purpose and benefits of diversion can reduce stigma and improve child rehabilitation. Diversion as an alternative to out-ofcourt settlement in the juvenile criminal justice system has great potential to protect children from the negative impacts of formal legal proceedings. However, challenges need to be overcome through education, training and community empowerment. Support from families and communities is critical to the successful rehabilitation and social reintegration of children in conflict with the law. With the right approach, it is expected that the implementation of diversion can be more effective in achieving restorative justice for children.